EVALUATION OF 18F-PSMA PET/CT UPTAKE IN PATIENTS WITH GASTRIC ADENOCARCINOMA: AN EXPLORATORY ANALYSIS - Renata Erbert Contriciani; Fabíola Furtuoso Zarpelão; Leo Victor Kim; Larissa Ariel Oliveira Carrilho; Sandra Regina Branbilla; Luiz Roberto Lopes; Nelson Adami Andreollo; Maria Emilia Seren Takahashi; Celso Dario Ramos; Maria Carolina Santos Mendes; Elba Cristina Sá de Camargo Etchebehere; José Barreto Campello Carvalheira (Hematology, Transfusion and Cell Therapy)
Introduction/Justification: Gastric cancer is the fifth most common cancer and the third leading cause of cancer-related death worldwide. The diagnosis of gastric tumors involves a multimodal approach, including upper gastrointestinal endoscopy with biopsy, computed tomography (CT), and endoscopic ultrasound. Positron emission tomography combined with computed tomography scanners (PET/CT) is widely used in cancer diagnosis and staging as it reflects the tumor's molecular activity. However, its indication in gastric cancer is limited, being reserved for specific clinical scenarios. In this context, evaluating new imaging methods for gastric tumors becomes crucial. In recent years, PET/CT targeting PSMA (Prostate-Specific Membrane Antigen) has been explored beyond prostate cancer. PSMA expression in the endothelium of newly formed vasculature (neoangiogenesis) has already been described in other cancer types, such as colorectal, gastric, and pancreatic; however, its role in gastric cancer evaluation remains poorly understood. Objectives: This study aims to investigate 18F-PSMA PET/CT uptake in different clinical scenarios of patients with gastric cancer and compare it with 18F-FDG PET/CT uptake (glucose metabolism). Materials and Methods: This study was approved by the Institutional Review Board (CAAE 76237023.0.0000.5404). It was conducted in patients diagnosed with gastric adenocarcinoma treated at the Clinic Hospital of Unicamp (HC-UNICAMP) who underwent both Fludeoxyglucose F-18 (FDG) and prostate-specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) to evaluate radiotracer uptake in the primary lesion and metastases. Results: A total of 24 patients with a confirmed diagnosis of gastric adenocarcinoma through upper gastrointestinal endoscopy and biopsy underwent 18F-PSMA PET/CT and 18F-FDG PET/CT. Among them, 5 had metastatic disease, and 19 had localized tumors. Among the 5 metastatic patients, 3 demonstrated PSMA uptake, of whom 2 had undergone chemotherapy before imaging, while 1 had not received chemotherapy prior to imaging. Among the 19 patients with localized tumors, 5 showed PSMA uptake, all of whom had not received neoadjuvant therapy. The remaining 14 patients showed no PSMA uptake, with 2 having undergone neoadjuvant therapy before the scan. Among these 14 patients without PSMA uptake, 6 also showed no FDG uptake, and only 1 had previously undergone neoadjuvant therapy. Conclusion: Our results demonstrated that PSMA uptake in gastric cancer is heterogeneous. It is well known that gastric cancer has high molecular, histological, and phenotypic heterogeneity, making its classification and treatment challenging. Accordingly, the findings of this descriptive analysis suggest that PET-PSMA uptake in gastric cancer may be associated with tumor biology, as well as the molecular profile of the tumor and its metastases, supporting the hypothesis that tumor heterogeneity contributes to the uptake or lack thereof of the radiotracer. Differential gene expression analysis may provide valuable insights into tumor heterogeneity and help identify potential biomarkers for patient stratification and the development of novel therapeutic approaches.